Multi-gene engineering in plants with RNA-guided Cas9 nuclease. (February 2016) - Raitskin, Oleg; Patron, Nicola J
Graphical abstract: Highlights: RNA-guided Cas9 nucleases have been employed for genome editing in several plant species. Several strategies for simultaneous expression of multiple sgRNAs have been demonstrated. Parallel DNA assembly methods enable rapid construction of vectors for plant genome editing. Abstract : The use of RNA-guided Cas9 endonuclease for the concurrent engineering of multiple genes has been demonstrated in a number of plant species. Although Cas9 is a large monomeric protein, the single guide RNA (sgRNA) that directs it to a specific DNA target sequence is small and easy to reprogram. It is therefore relatively simple to produce numerous sgRNAs to target multiple endogenous sequences. Several approaches to express multiple sgRNAs and Cas9 in plants for the purpose of simultaneous editing or transcriptional regulation of many genes have recently been reported.